A Simple Sector Independent Space Vector Modulation Technique Implemented using a DSP Processor - Susovan Mukhopadhyay; Sujit Kumar Biswas; Nirmal kumar Deb (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper presents the software implementation of a simple sector independent Space Vector Modulation (SVPWM) technique for simple motor drive applications using DSP processor. The closed loop control scheme with Volts/Hz principle, suitably regulates the switching period and operates with a fixed set of compare register values. The Space Vector Pulse Width Modulation hardware module on the TI TMS320LF2407A is used to produce the Pulse Width Modulated (PWM) pulses with four switching states in one PWM period. In contrast to the conventional scheme, the algorithm developed here, eliminates the computational burden involved in determining the magnitude and phase of the voltage vector, the corresponding sector and the decomposition matrices for calculating the switching time segments. A 1hp, 3 phase induction motor fed from an IGBT based inverter module is tested with the control pulses generated from the DSP processor and the performance is found to be satisfactory.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.348